The Culture of Research: A Systematic Scoping Review - Elena Tikhonova; Lilia Raitskaya (National Research University Higher School of Economics, 2024)
Introduction: Research culture is the core of many processes in science. It is a broad concept presumably entailing practices, traditions, norms, etc. that prevail among researchers and other stakeholders in the field. Its definition, architecture, and taxonomy are essential in generating and pursuing scientific policies at universities and countries. As there is a lack of comprehensive reviews on research culture, the present publication aspires to fill the existing gap in the knowledge. This review aims to define research culture and build an architecture of research culture based on the relevant literature indexed in the Scopus database. Method: The problem, concept, and context (PCC) framework was applied to establish an effective search strategy and word the research questions corresponding to the aim. Based on Arksey and O'Malley's methodology (2005) and PRISMA checklist (2020) for systematic reviews, the authors sorted out 56 relevant publications for systematic scoping review. In addition, a bibliometric analysis was applied to examine the field. Results: Using a bibliometric analysis, the 56 publications were distributed by year, country, most prolific authors, sources, research fields, affiliation, and type of publication. With the help of VOSviewer, the authors singled out four thematic clusters (research culture; medical and biomedical research, methodology and research ethics, and clinical studies and human experiments). After synthesizing the data extracted from the documents under review, research culture was defined; components of research culture were singled out and summed up; and a framework of research culture was made up. The authors analysed the review findings in contrast with other research, offering their own comprehensive definition of research culture, its taxonomy, and an architecture of research culture.  Conclusion: The current review adds to the understanding of research culture, its gist, component classification. The limitation related to the period of review (2019-2024) may be overcome by further reviews of relevant publications from a historic perspective that would broaden perceptions of the origin of modern research culture and its negative aspects.